2004
DOI: 10.1046/j.1365-2516.2003.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus inactivation by the solvent/detergent steps of the second and third generation manufacturing processes for B‐domain deleted recombinant factor VIII

Abstract: West Nile Virus (WNV) was immediately and completely inactivated to below assay detection limits upon addition of solvent/detergent (S/D) to intermediate process pools of second and third generation B-domain deleted recombinant Factor VIII (BDDrFVIII; ReFacto, Wyeth, Cambridge, MA, USA). We verify that the S/D step provides robust enveloped virus inactivation (>5 log(10)) and functions as a WNV barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…After the finding that WNV can be transmitted through blood and blood components, the production processes of plasma derivatives were investigated using WNV. It was demonstrated that in the validation studies WNV behaved comparable to other enveloped viruses belonging to the Flaviviridae used as model viruses for the validation of manufacturing processes (bovine viral diarrhea virus (BVDV) and TBEV) [40,203,204]. In inactivation studies, a reduction of the infectious virus titers by a factor of 10 4 was shown for WNV as well as for the model viruses.…”
Section: Methods For Removal and Inactivation Of The Infectious Agentmentioning
confidence: 99%
“…After the finding that WNV can be transmitted through blood and blood components, the production processes of plasma derivatives were investigated using WNV. It was demonstrated that in the validation studies WNV behaved comparable to other enveloped viruses belonging to the Flaviviridae used as model viruses for the validation of manufacturing processes (bovine viral diarrhea virus (BVDV) and TBEV) [40,203,204]. In inactivation studies, a reduction of the infectious virus titers by a factor of 10 4 was shown for WNV as well as for the model viruses.…”
Section: Methods For Removal and Inactivation Of The Infectious Agentmentioning
confidence: 99%
“…The flaviviruses used in the individual process steps (bovine viral diarrhea virus, TBEV, DENV, and WNV) have a comparable sensitivity to solvents and detergents (SD method), low pH, or heat treatment [28,30,[144][145][146][147].…”
Section: Methods For Removal and Inactivation Of The Infectious Agentmentioning
confidence: 99%
“…Based on the studies available up to now, all flaviviruses tested (bovine virus diarrhoea virus, FSMEV, WNV) are sensitive to the inactivation methods used [14,19,73]. Pooled plasma treated with the solvent/detergent methods is safe, since flaviviruses and other enveloped viruses are effectively inactivated [[74] (review)].…”
Section: Blood Productsmentioning
confidence: 99%